A neuroscientific perspective on basic psychological needs. Issue 1 (20th May 2018) - Reeve, Johnmarshall; Lee, Woogul
Abstract: Objective: Self‐determination theory's (SDT) most basic propositions are, first, that all people possess an inherent set of psychological needs and, second, that autonomy, competence, and relatedness are the three critical psychological satisfactions needed to maintain and promote personal growth and well‐being. In this article, we identify the neural basis of the psychological needs and, in doing so, seek to advance the integration of SDT and neuroscience. Method: We examine the neural underpinnings of SDT‐based motivational states and traits for autonomy, competence, and relatedness. To study motivational states, participants are exposed to situational conditions known to affect their psychological needs, and neuroscience methods (e.g., fMRI) are used to examine changes in their brain activity. To study motivational traits, participants complete self‐report trait measures that are then correlated with their brain activity observed during need‐satisfying activities. Results: For both motivational states and traits and across all three needs, intrinsic satisfaction is associated with striatum‐based reward processing, anterior insula–based subjective feelings, and the integration of these subjective feelings with reward‐based processing. Conclusions: Psychological need satisfaction is associated with striatum activity, anterior insula activity, and the functional coactivation between these two brain areas. Given these findings, it is now clear that several opportunities exist to integrate SDT motivational constructs with neuroscientific study, so we suggest eight new questions for future research.